Hubungan Dukungan Keluarga Dengan Resiliensi Pada Narapidana Di Lembaga Pemasyarakatan Perempuan Kelas II B Padang - Salsa Saptania (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Prisoners are vulnerable to mental disorders and low resilience, making it difficult for them to overcome life's challenges. Family support plays an important role in improving prisoner resilience. This study aimed to determine the relationship between family support and resilience among inmates at the Class II B Women's Correctional Institution in Padang in 2025. This was a quantitative descriptive-analytic study with a cross-sectional approach, involving 64 respondents selected through simple random sampling. Data were collected on July 25, 2025 using questionnaires and analyzed with the chi-square test (p < 0.05). The results showed that 43.8% of inmates had low resilience, 31.3% moderate, and 25.0% high; while 18.8% reported low family support, 53.1% moderate, and 28.1% high. A significant relationship was found between family support and resilience among inmates (p-value = 0.000). This study is expected to guide correctional leaders in improving inmate resilience through family support.